Effect of L-alanyl-glycine dipeptide on calcium oxalate crystallization in artificial urine - POLAT, SEVGİ (ELSEVIER, 2021)
Pathological crystallization of calcium oxalate (CaOx), the most common constituent of kidney stones, has attracted much attention due to recent surge in reported natural and synthetic additives effectively inhibiting its nucleation and growth. The aim of this study is to investigate the effect of L-alanyl-glycine (Ala-Gly), a dipeptide commonly found in human urine, on CaOx crystallization and its phase transformation in the presence of an artificial urine media. The nucleated CaOx crystals are characterized by XRD, FTIR, SEM, and dynamic light scattering in terms of changes in their crystalline form, morphology, and size. XRD and FTIR results revealed that Ala-Gly inhibited the formation of the thermodynamically most stable phase of CaOx, calcium oxalate monohydrate (COM) crystals. SEM images revealed that hexagonal plate-shaped COM crystals are transformed into the smaller tetragonal bipyramidal calcium oxalate dihydrate (COD) crystals with increasing additive concentrations. At 125 ppm Ala-Gly concentration more pronounced aggregation of CaOx crystals is observed accompanied with higher negative zeta potential value of -27.1 +/- 2.9 mV. Moreover, the phase transformation from COM to COD is also confirmed through thermogravimetric analysis. Consequently, these results suggest that Ala-Gly has a profound effect on preventing the formation of COM crystals and helping to stabilize the COD crystals, a CaOx phase that is reported to have a lower tendency to stick to kidney cells thus decreasing the risk of stone formation. The reported suppression of COM in the presence of Ala-Gly might be significant to clinicians in their attempt to develop a long-term effective treatment for kidney stones.
Keywords: B1; Calcium oxalate monohydrate; B1; Calcium oxalate dihydrate; A1; Crystal Morphology; B1; Crystallization; A1; Phase transformation; KIDNEY-STONE; CRYSTAL-STRUCTURE; THERMAL-TREATMENT; AMINO-ACIDS; MONOHYDRATE; PROTEINS; GROWTH; POLYPEPTIDES; WHEWELLITE; WEDDELLITE